2021
DOI: 10.1080/01616412.2021.1948768
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravascular therapy in patients with progressive stroke caused by intracranial large vascular occlusion exceeding the time window of 24 hours

Abstract: Purpose: To compare endovascular and drug therapies for efficacy and safety in patients with a progressive stroke caused by intracranial large vascular occlusion exceeding the time window of 24 hours. Patients and methods: A total of 58 patients with progressive stroke caused by large intracranial vascular occlusion exceeding the time window of 24 hours treated in the stroke center of our hospital for three years were retrospectively analyzed . According to the applied therapy, 58 patients were divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Improper heparin dosage and elevated blood pressure are important causes of postoperative intracranial hemorrhage. Vascular reopening and high perfusion can also cause secondary damage to the brain tissue, resulting in brain edema and intracranial hypertension[ 16 , 17 ]. Therefore, prevention and nursing of postoperative complications are key to the success of interventional surgery and rehabilitation of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Improper heparin dosage and elevated blood pressure are important causes of postoperative intracranial hemorrhage. Vascular reopening and high perfusion can also cause secondary damage to the brain tissue, resulting in brain edema and intracranial hypertension[ 16 , 17 ]. Therefore, prevention and nursing of postoperative complications are key to the success of interventional surgery and rehabilitation of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The published literature reports outcomes of endovascular therapy in patients with progressive stroke in the anterior circulation compared with standard drug therapy. In trials of endovascular therapy for progressive ischemic stroke in anterior circulation large artery occlusion, the overall outcome of EVT was significantly better than drug therapy, even beyond the traditional 24-h time window, and endovascular therapy may improve neurological recovery within 90 days ( 9 , 10 ). Relatively few studies have been reported on patients with progressive stroke in BAO.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the effectiveness and safety of EVT in patients with progressive stroke due to large vessel occlusion in the anterior circulation. EVT has a better outcome than SMT without increasing the incidence of adverse events ( 9 , 10 ). And although EVT has been used in the past few years to treat BAO with a trend toward benefit, there are limited data on the efficacy and safety of EVT in progressive stroke.…”
Section: Introductionmentioning
confidence: 99%